PENGARUH VISUAL APPEAL DAN SUBJECTIVE NORMS TERHADAP IMPULSE BUYING DENGAN DIMEDIASI OLEH PERCEIVED ENJOYMENT DAN DIMODERASI OLEH USER EXPERIENCE (STUDI PADA PENGGUNA SHOPEEPAY DI KOTA MALANG) - Hasbi Mustopa Kamil Sabani; Nur Laili Fikriah (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
The objective of this study is to explore how visual appeal and subjective norms impact impulse buying, with perceived enjoyment as a mediator and user experience as a moderator among ShopeePay users in Malang City. This research adopts a quantitative approach with a descriptive methodology. The study's population includes ShopeePay users in Malang City, with a sample of 95 participants. Data were gathered through online questionnaires, and analysis was conducted using Smart PLS version 4.0. The findings reveal that visual appeal and subjective norms have a significant effect on perceived enjoyment. Furthermore, both subjective norms and perceived enjoyment significantly influence impulse buying. Perceived enjoyment also mediates the effects of visual appeal and subjective norms on impulse buying. However, the effect of visual appeal on impulse buying was found to be non-significant. Additionally, user experience does not act as a moderating variable in the relationship between perceived enjoyment and impulse buying. Overall, the research hypotheses are supported with the exception of the link between visual appeal and impulse buying and the moderating role of user experience. Keywords: visual appeal; subjective norms; perceived enjoyment; user experience; impulse buying. Tujuan penelitian ini adalah untuk mengkaji hubungan visual appeal dan subjective norms terhadap impulse buying, yang dimediasi oleh perceived enjoyment dan dimoderasi oleh user experience pada pengguna ShopeePay di Kota Malang. Penelitian ini menggunakan metodologi kuantitatif dengan pendekatan deskriptif. Populasi penelitian terdiri dari pengguna ShopeePay di Kota Malang dengan sampel 95 responden. Teknik pengumpulan data menggunakan penyebaran kuesioner online. Analisis data menggunakan Smart PLS versi 4.0. Hasil penelitian membuktikan bahwa visual appeal dan subjective norms memiliki pengaruh signifikan terhadap perceived enjoyment. Subjective norms dan perceived enjoyment berpengaruh signifikan terhadap impulse buying. Selanjutnya, perceived enjoyment menediasi hubungan anatar visual appeal dan subjective norms atas impulse buying. Namun, pengaruh visual appeal atas impulse buying tidak signifikan. Terakhir, user experience tidak memberikan pengaruh moderasi atas perceived enjoyment atas impulse buying. Kesimpulannya, hipotesis penelitian didukung kecuali untuk hubungan antara visual appeal dan impulse buying, serta peran user experience sebagai variabel moderasi. Kata kunci: visual appeal; subjective norms; perceived enjoyment; user experience; impulse buying.